2023
DOI: 10.1371/journal.pone.0283749
|View full text |Cite
|
Sign up to set email alerts
|

Axl contributes to efficient migration and invasion of melanoma cells

Abstract: Axl, a member of the TAM receptor family has been broadly suggested to play a key role in tumor metastasis. However, the function of Axl in the invasion and metastasis of melanoma, the most lethal skin cancer, remains largely unknown. In the present study, we found that melanoma cell lines present variable protein levels of Axl and Tyro3; interestingly, MerTK is not noted at detectable levels in any of tested MGP (metastatic growth phase) cell lines. Treatment with recombinant human Gas6 significantly activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In many cancer types AXL expression has been associated with an epithelial to mesenchymal (EMT) transition and invasiveness (Asiedu et al, 2014; Boshuizen et al, 2018; Shao et al, 2023; Wang et al, 2016) and is linked to worse prognosis and resistance to therapies in a wide range of cancers including prostate (Bansal et al, 2015), breast (Creedon et al, 2014), lung (Zhang et al, 2012), renal (Zhou et al, 2016), head and neck (Elkabets et al, 2015) and neuroblastoma (Debruyne et al, 2016). Consequently, AXL has attracted increasing attention as a candidate for therapy (Auyez et al ., 2021; Colavito, 2020; Gay et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In many cancer types AXL expression has been associated with an epithelial to mesenchymal (EMT) transition and invasiveness (Asiedu et al, 2014; Boshuizen et al, 2018; Shao et al, 2023; Wang et al, 2016) and is linked to worse prognosis and resistance to therapies in a wide range of cancers including prostate (Bansal et al, 2015), breast (Creedon et al, 2014), lung (Zhang et al, 2012), renal (Zhou et al, 2016), head and neck (Elkabets et al, 2015) and neuroblastoma (Debruyne et al, 2016). Consequently, AXL has attracted increasing attention as a candidate for therapy (Auyez et al ., 2021; Colavito, 2020; Gay et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a combined therapy involving a BRAF/MEK inhibitor along with an AXL inhibitor is being considered for enrollment in a clinical trial [67]. In vitro studies have shown that AXL silencing via siRNA or pharmacological inhibition dramatically impedes the migration and invasion of melanoma cells [68]. The inhibition of uPAR expression using a specific uPAR antisense oligonucleotide has been found to inhibit cell invasion, angiogenesis, metastasis, and MMP expression [44,69].…”
Section: Discussionmentioning
confidence: 99%
“…AXL, a tyrosine kinase receptor, is another potential target due to its notable elevated expression in many cancers, including melanoma [29,58]. Once bound by a ligand, AXL will activate downstream signaling pathways that affect cell cycle progression, including the PI3K/AKT pathway.…”
Section: Non-braf and Mek-related Biomarkersmentioning
confidence: 99%
“…AXL expression is also correlated with acquired MAPK resistance [29], including BRAFi/MEKi double resistance, and targeting AXL cooperatively inhibited tumor growth with BRAF/MEK inhibitors in patient-derived xenografts [60]. Recent in vitro studies have shown that the knockdown of AXL by siRNA or its inhibitor bemcentinib in melanoma cells decreased migration and invasion [58,61]. A phase II study (NCT02872259) comparing the efficacy of the standard melanoma treatment of dabrafenib, trametinib, and pembrolizumab with or without bemcentinib in patients with phase III or IV melanoma is currently ongoing [62].…”
Section: Non-braf and Mek-related Biomarkersmentioning
confidence: 99%